Developing an E-module to Train Class 10 High School Students' Argumentation Skills in the Material of Spermatophyte Plants Using the Argument-Driven Inquiry Learning Model - Hana Hanifa Minawati; Eling Purwantoyo (Journal of Biology Education, 2026)
Argumentation skills are very important in the 21st century communication skills that students need to master. Technological advances in the 21st century need to be utilized to make teaching materials more effective. Based on the results of interviews with biology teachers at SMA N 12 Semarang, learning biology only uses LKS books with assistance power point and YouTube. The scores of some students in Spermatophyte plant material at basic competency 3.8 and basic competency 4.8 have not fulfilled the KKM (Minimum Completeness Criteria) because learning is still centered on the teacher and causes students' argumentation skills to be untrained. Therefore, teaching materials in the form of e-modules were developed to train class 10 students' argumentation skills in Spermatophyte material using a learning model Argument-Driven Inquiry (ADI). E-module is a teaching material that is arranged systematically that encourages students to learn independently. The ADI Learning Model can train students' argumentation skills. This study aims to analyze the validity, practicality, and effectivenesse-module to train students' argumentation skills. This type of research is research and development (RnD) with the ADDIE (Analysis, Design, Development, Implementation, and Evaluation) development model. Validity data of e-module obtained from the media and material validation questionnaire. Practical data of e-module obtained from student readability, student and teacher response questionnaires. Effectiveness data of e-module obtained from student activity sheets and questions pretest-posttest determined by the test results Mann-Whitney, Wilcoxon, and N-Gain. Results of validity analysis e-module from the validation of media experts and the material is stated to be very valid. The results of practicality research e-module from the results of the readability test analysis it was stated that it was practical, the results of the analysis from the student responses were 76% (practical) and the teacher's response was 81.3% (very practical). Effectiveness e-module of results N-Gain In the experimental class it is known that only 8% of students are in the high category and 14% of students are in the low category which shows that learning uses e-module ineffective. The student's argumentation skill level reaches level 2. Test Mann-Whitney showed that there was a significant difference in learning outcomes between the control and experimental classes. Wilcoxon test shows a significance value in the experimental class of 0.486>0.05, which means learning to use e-module not effective for improving student learning outcomes. The conclusions of this study are the validity and practicality of e-module very valid and practical for learning, but not effective for increasing the value of learning outcomes.